2009
DOI: 10.1093/carcin/bgp067
|View full text |Cite
|
Sign up to set email alerts
|

PLAB induction in fenretinide-induced apoptosis of ovarian cancer cells occurs via a ROS-dependent mechanism involving ER stress and JNK activation

Abstract: Fenretinide [N-(4-hydroxyphenyl)-retinamide (4HPR)] is a synthetic retinoid with antitumor activity that induces apoptosis in various types of cancer cell. We showed previously that 4HPR upregulates the proapoptotic gene placental bone morphogenetic protein (PLAB), which is a mediator of 4HPR-induced apoptosis in ovarian cancer cells. Here, we investigated the signaling cascade involving PLAB that mediates the apoptotic effect. In 4HPR-sensitive ovarian cancer cells, 4HPR-induced reactive oxygen species (ROS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…This is in agreement with previous reports that in Toxoplasma gondii infection, ROS-triggered trophoblast apoptosis is initiated by ER stress via activation of the JNK pathway along with caspase-12 and CHOP (52). A study demonstrated that fenretinide, a synthetic retinoid with antitumor activity, induced PLAB protein upregulation involving ROS generation, ER stress induction, and JNK activation (53). The role of ROS in TNFinduced apoptosis is also well known (54).…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous reports that in Toxoplasma gondii infection, ROS-triggered trophoblast apoptosis is initiated by ER stress via activation of the JNK pathway along with caspase-12 and CHOP (52). A study demonstrated that fenretinide, a synthetic retinoid with antitumor activity, induced PLAB protein upregulation involving ROS generation, ER stress induction, and JNK activation (53). The role of ROS in TNFinduced apoptosis is also well known (54).…”
Section: Discussionsupporting
confidence: 91%
“…There is an integrated system to clear ROS in the body to keep balance. Oxidation of cell membrane phospholipids, enzymes and DNA (37,38) by high levels of ROS can alter the function of signal transduction pathways, platelet aggregation, immune control, and the regulation of cell growth, and can also cause necrosis or apoptosis (39,40). Since the generation of ROS is the result of disordered mitochondria function and metabolite augmentation, there may be ways to regulate ROS selectively in cancer cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…There is an integrated system of clearing ROS in the body to keep balance. Oxidation of cell membrane phospholipids, enzyme, and DNA [24][25][26][27] by high levels of ROS can alter function of signal transduction, platelet aggregation, immune control, and the regulation of cell growth, and they can also cause necrosis or apoptosis [28][29][30][31]. As the generation of ROS is the result of disordered functioning of mitochondria and metabolite augmentation, there may be ways to regulate ROS selectively in cancer cells [12,32].…”
Section: Discussionmentioning
confidence: 99%